What about new entry? Examining the theorized role of new entry in the entrepreneurial orientation–performance relationship. (June 2015) - Wales, William; Wiklund, Johan; McKelvie, Alexander
It has been well over a decade since Lumpkin and Dess first suggested new entry to represent the principal outcome of an entrepreneurial orientation (EO). Yet, little consideration has been given to the implications of conceptualizing new entry as a phenomenon distinct from EO. This article draws attention to inconsistent assumptions concerning the role of new entry across the two dominant conceptualizations of EO, discusses empirical challenges with exploring new entry as an outcome of EO, and provides a longitudinal test of the causal chain linking EO to future new entry behaviors and eventual performance outcomes.